#### Answer

x=6

#### Work Step by Step

Simplifying
4x + 2(x + 3) = 42
Reorder the terms:
4x + 2(3 + x) = 42
4x + (3 * 2 + x * 2) = 42
4x + (6 + 2x) = 42
Reorder the terms:
6 + 4x + 2x = 42
Combine like terms: 4x + 2x = 6x
6 + 6x = 42
Solving
6 + 6x = 42
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6' to each side of the equation.
6 + -6 + 6x = 42 + -6
Combine like terms: 6 + -6 = 0
0 + 6x = 42 + -6
6x = 42 + -6
Combine like terms: 42 + -6 = 36
6x = 36
Divide each side by '6'.
x = 6
Simplifying
x = 6